Above-ground biomass and carbon storage in awat-awat mangrove forest, Malaysia - Arianto, Chandra Iman (2013)
Mangroves are coastal forests that affects by tides, soil texture and marine salinity which is found in tropical and subtropical coastal tidal regions. They are very well adapted to grow in sea and brackish water. They presently cover about 20 million hectare worldwide and contain large amount of carbon both within vegetation and soil. Mangrove forests in Malaysia, especially in Sarawak is about 175,153 ha which are found along the coastline and values of both monetary and non-monetary. Mangroves play an important role in global carbon cycling and in relation to climate change mitigation, since they hold a large pool of carbon as well as potential carbon sinks and sources to the atmosphere. Furthermore, mangroves also useful to stabilize shorelines and reducing damage of natural disaster. Study of mangroves have been done extensively but remain poorly understood but because of continuing degradation and destruction of mangroves, a better understanding how valuable mangroves is critically needed. This study is very important to gain information and experience through quantify biomass and carbon storage of R. apiculata using non harvesting technique (allometry) so in the future the quantification of biomass of mangrove forest through harvesting technique can be avoided and the proper management system based on the sustainable yield principle can be establish. In this study, seven species have been found in Awat-Awat mangrove forest with the dominance of R. apiculata. Assessment of above-ground biomass production of Rhizophora apiculata samples in Awat-Awat mangrove forest, Sarawak, Malaysia has been taken and based on those data, the fit allometric equation to quantify the total above-ground was formulated. The first part of this study was to determine above-ground biomass production and stem volume of R. apiculata. Seven representative trees were used in this study for sampling. Allometric relationships were examined using either independent variable diameter (D) or combination of quadratic of D and Height (D²H). The best fit of allometric equations were developed from the combination of quadratic of D and H (y = 0.0409x1.002, R²=0.98) which is more recommended to estimate biomass and stem volume of R. apiculata in Awat-Awat mangrove forest, Sarawak. Furthermore, the total aboveground biomass and stem volume of R. apiculata were 138.20 t ha-1 and 65.55 m3 ha-1, respectively. It found that aboveground biomass and stem volume is closely related with tree diameter and height which indicates that aboveground biomass and stem volume will increase with increasing diameter and height of R. apiculata. The second part of this study was to determine carbon sequestration of R. apiculata in Awat-Awat mangrove forest, Sarawak, Malaysia. The total carbon content R. apiculata tree components was analyzed using CHNS analyzer (TruSpec Micro Elemental Analyzer (NCHS), LECO, USA). Total carbon content of tree component of R. apiculata in Awat-Awat mangrove forest at Lawas, Sarawak, Malaysia ranged from 39.96±0.890 % to 44.71±0.189 %. Big diameter class of R. apiculata has the highest proportion in total carbon content of R. apiculata in Awat-Awat mangrove forests whereas the highest proportion contributor for total carbon content of R. apiculata in Awat-Awat mangrove forest was branch followed by stem, prop-root and leaf components. The amount of total carbon sequestration of R. apiculata in Awat-Awat mangrove forest, Malaysia was 60.71 MgC ha-1 with the stem as the highest contributor followed by branch, prop-root, and leaf, respectively. The last part of this study was to determine soil carbon storage in Awat-Awat mangrove forest, Sarawak, Malaysia. Soil of Awat-Awat mangrove forest was collected randomly in each zone using a peat auger at a depth of 0 to 30 cm and a total of 40 samples were collected. The total carbon content of soil samples was analyzed using CHNS analyzer (TruSpec Micro Elemental Analyzer (NCHS), LECO, USA). Soil total carbon of Awat-Awat mangrove forest was varied in three zones. The soil total carbon and organic matter of Awat-Awat mangrove forest, Malaysia was found highest in the landward zones whereas the lowest was found in the middle zones. Soil total carbon and soil organic matter of Awat-Awat mangrove forest, Malaysia were 2.64% and 4.5%, respectively. Furthermore, it is believed that there is a significant difference among mangrove soils due to the presence of different mangrove species.